Perkuatan Balok Beton Bertulang Yang Mengalami Kegagalan Geser Menggunakan Metode Deep Embedment - Kurniawan, Fahmuji; Kamaldi, Alfian; Yuniarto, Enno; Ridwan (Dept. of Civil Engineering Universitas Riau, 2023)
Bridges are infrastructure buildings that are commonly used and very functional in everyday. One of the structural components of the bridge is a reinforced concrete beam as a load bearer that will be forwarded to the foundation. The shear capacity of reinforced concrete beam structures sometimes cannot meet the existing requirements. This can be caused by increased loads, inadequate shear strength in the initial design and material damage due to natural factors. There are several methods that have been carried out to overcome the decrease in shear strength in beam structures, namely reinforcement methods by externally bonded (EB) and near-surface mounted (NSM). In reality, shear reinforcement with EB and NSM methods in implementation only relies on epoxy adhesion and concrete blankets, which still causes structural failure. The deep embedment strengthening method (DE) can be proposed as a shear reinforcement for reinforced concrete beams to overcome the previous problems. Reinforcement with DE method is a shear reinforcement that is reinforced in the core of reinforced concrete beams. This research was conducted by embedding 8 reinforcements vertically with a distance of 200 mm along the shear span. In this study, finite element modeling was carried out using ABAQUS. The results of finite element modeling with the DE method showed that the maximum load was 30.646 kN and the maximum deflection was 13.00 mm. The collapse model that occurs from finite element modeling on test specimens with DE reinforcement experiencing flexural failure.